High‐Performance Flexible Organic Nonvolatile Memories with Outstanding Stability Using Nickel Oxide Nanofloating Gate and Polymer Electret - Yeon‐Ju Kim; Minji Kang; Min‐Hye Lee; Ji‐Sue Kang; Dong‐Yu Kim (Advanced Electronic Materials)
Abstract Organic nonvolatile memory devices based on organic field‐effect transistors (OFETs) have attracted attention as promising memory components in flexible organic integrated circuits. OFET‐based organic memories can be fabricated using solution processes with high portability and flexibility. However, many challenges still remain, such as achieving high levels of transparency and data storage while maintaining device reliability. In this study, the high‐performance of flexible organic nonvolatile memory devices is demonstrated through the synergistic effect of using a combination of polymer electret (poly(2‐vinyl naphthalene), PVN) and nanofloating gates (nickel oxide nanoparticles (NiOx NPs)). The PVN/NiOx NPs bilayer successfully acts as a charge storage medium with high transparency in the visible range. This system greatly improves memory performance including high data storage capacity, stable cyclic endurance, and quasi‐permanent retention characteristics (>10 years). Furthermore, these devices also show excellent charge storage characteristics after 1000 bending cycles and even under the sharply bent state (bending radius 3 mm). This enhanced mechanical stability of flexible synergistic memory devices demonstrates that NiOx NPs can play an important role as a reliable data storage material for next‐generation wearable electronic devices.